f(x) = 5x − 1 and g(x) = 2x^2 + 1
(f × g)(x) = (5x − 1)(2x^2 + 1)
(f × g)(x) = 10x^3 - 2x^2 + 5x - 1
Substitute x = - 3
(f × g)(-3) = 10(-3)^3 - 2(-3)^2 + 5(-3) - 1
(f × g)(-3) = 10(-27) - 2(9) -15 - 1
(f × g)(-3) =-270 - 18 - 16
(f × g)(-3) = -236
Answer
- 236
Are you trying to convert the percentages into fractions or??
Answer:
93107
Step-by-step explanation:
add all of the numbers together
divide by 5 since there are 5 numbers
you would get 92106.8
so round that up since you cannot have 1/8 of a squirrel
Hope this helps!!
ANSWER:
15 SLICES
Explanation:
Joe ate 2 slices (1/4 = 2/8), Rhoda ate 3 (3/8), Chris ate 4.
2+3+4= 9.
There are 3 pizzas divided into 8 slices per pizza.
3 x 8 = 24 ; 24 SLICES TOTAL
Subtract 9 (that’s what was consumed) from 24.
24-9 = 15 ; 15 SLICES LEFT OVER
pls mark brainliest hehe